2009
DOI: 10.1159/000210042
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Maintenance Treatment during Pregnancy: Occurrence and Severity of Neonatal Abstinence Syndrome

Abstract: Background: Opioid maintenance treatment (OMT) is widely used to treat pregnant women with a history of opioid dependence. This study investigated whether maternal methadone/buprenorphine dose and nicotine use in pregnancy affects the occurrence and duration of neonatal abstinence syndrome (NAS) in the infant. Methods: Forty-one pregnant women from OMT programmes in Norway who gave birth between January 2005 and January 2007 were enrolled in a national prospective study. Thirty-eight women (81% of the populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 65 publications
7
118
3
2
Order By: Relevance
“…[38][39][40] Multiple studies demonstrated that buprenorphine maintenance treatment in pregnancy is either comparable or superior to methadone treatment with regard to NAS; however, these studies were observational, retrospective, or small (Supplemental Table 5). [41][42][43][44][45][46][47][48] A larger prospective randomized study favored buprenorphine over methadone with regard to the doses and durations of morphine treatment and lengths of hospital stays, but not the incidence nor the severity of NAS. 49 A recent meta-analysis did not favor one over the other.…”
Section: Growing Epidemiologymentioning
confidence: 99%
“…[38][39][40] Multiple studies demonstrated that buprenorphine maintenance treatment in pregnancy is either comparable or superior to methadone treatment with regard to NAS; however, these studies were observational, retrospective, or small (Supplemental Table 5). [41][42][43][44][45][46][47][48] A larger prospective randomized study favored buprenorphine over methadone with regard to the doses and durations of morphine treatment and lengths of hospital stays, but not the incidence nor the severity of NAS. 49 A recent meta-analysis did not favor one over the other.…”
Section: Growing Epidemiologymentioning
confidence: 99%
“…Much information collected for this study was based on maternal self-report, which could result in inaccurate or socially desirable reporting. While drug and alcohol use may be underreported in self-report measures, the results from frequent urine controls during pregnancy suggests otherwise, as they were generally in agreement with self-report measures (Bakstad et al, 2009). Because both the outcome measure (CBCL) and independent maternal variables were mainly based on self-report, results may have been affected by similarities in the way the mothers responded on these questionnaires.…”
Section: Discussionmentioning
confidence: 93%
“…Neonatal data, including gestational age, birth weight, birth length, head circumference, and NAS was obtained from each child's medical record at birth. NAS was assessed using the modified Finnegan neonatal abstinence score or the Lipsitz score (see also Bakstad et al, 2009). Maternal drug and alcohol use as well as methadone or buprenorphine dose during pregnancy was measured with a structured interview administered in the last trimester of pregnancy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations